Pengembangan Self Awareness Santriwati Melalui Refleksi Diri dan Visualisasi Pohon Mimpi di Pondok Pesantren Daruz Zahro’ Assunniyyah Kabupaten Lumajang - Amalia Eka Putri; Fauziah Della Paramitha; Racquel Akiela Kalila; Mafda Khoirotul Fatha; Rahma Aji Dwi Nastiti; Fazlul Rahman (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to examine the effectiveness of the implementation of self-reflection activities combined with dream tree visualization media in supporting the development of self-awareness of female santri in one of the boarding schools in Lumajang Regency. Self-awareness is seen as a crucial component in adolescent character building, especially in the context of boarding school-based education that emphasizes the value of spirituality and discipline. The participants in this study amounted to around 30 female students from junior high school to vocational school. Data were collected through field observations, implementation of reflective seminars, and documentation of the results of dream tree visualization made by participants. The findings show that the integration of self-reflection and dream trees is able to increase participants' self-awareness of their potential, life values, and the future direction they want to achieve. In addition, this method also strengthens the spiritual dimension and sense of responsibility of santriwati towards life goals in line with Islamic teachings. Based on these results, it is recommended that this approach be implemented sustainably in the counseling guidance program in the boarding school environment.